2014
DOI: 10.1016/j.phpro.2014.08.115
|View full text |Cite
|
Sign up to set email alerts
|

Ablation Study of WC and PCD Composites Using 10 Picosecond and 1 Nanosecond Pulse Durations at Green and Infrared Wavelengths

Abstract: An ablation study is carried out to compare 10 picosecond and 1 nanosecond pulse durations as well as 532 nanometre and 1064 nanometre wavelengths at each corresponding pulse duration. All laser parameters are kept constant in order to understand the influence of pulse duration and wavelength independently. The materials processed according to the electronic band structure are a metal and an insulator/metal composite, i.e. tungsten carbide and polycrystalline diamond composite respectively. After laser process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A graphite layer is found to exist beneath the ablated top surface. Nonetheless, under ultra-short pulsed laser ablation, the graphitization process is more obscure, depending on the pulse length or fluence according to different papers [18][19][20] . The potential allotropic transformation of the diamond structure after laser ablation is a critical aspect for the development of a laser polishing process.…”
Section: Interaction With Pcd Composition and Structurementioning
confidence: 99%
“…A graphite layer is found to exist beneath the ablated top surface. Nonetheless, under ultra-short pulsed laser ablation, the graphitization process is more obscure, depending on the pulse length or fluence according to different papers [18][19][20] . The potential allotropic transformation of the diamond structure after laser ablation is a critical aspect for the development of a laser polishing process.…”
Section: Interaction With Pcd Composition and Structurementioning
confidence: 99%
“…The advantages of this are higher ablation rates with better precision. Eberle et al [ 59 ] ablated PCD-Co10% and WC-Co4.6% at 2 distinct wavelengths: 532 nm and 1064 nm. The ablation rate was consistently higher at different fluences and pulse durations when the 532 nm was used ( Figure 7 b,c).…”
Section: Fabrication Of Surface Texturesmentioning
confidence: 99%
“… ( a ) Overview of material behaviour at different wavelengths, ( b ) Ablation rate for PCD. ( c ) Ablation rate for WC [ 59 ] (copyright permission from Elsevier). …”
Section: Figurementioning
confidence: 99%
“…The chip breaker was manufactured using a nano-second laser, the ablation process was performed with a SPI-G4-HS ns ytterbium-doped fiber laser, Hedge End, Southampton, United Kingdom, emitting pulses at a wavelength of 1064 nm and using a mean power value of around 40 W. It has been reported that the ablation of PCD using ns pulses takes place via graphitization of the diamond in the PCD which is transformed into graphitic carbon [41]. The proportionality between the graphite-layer thickness, the pulse duration and the laser fluence has been proven [42].…”
Section: Manufacturing Of the Chip Breakermentioning
confidence: 99%